Slit Lamp Biomicroscopy - William Randolph Morris (Association of American Medical Colleges, 2012)
Abstract This resource is a video showing ocular examination techniques utilizing slit lamp biomicroscopy. It has been distributed to first-year ophthalmology residents at our institution as part of their orientation. It would also be useful to other medical practitioners such as emergency room and family medicine physicians who might use this instrument in their practice. This resource was created using a combination of video footage, slit lamp photographs, and simple animations. The author believes that the user of the slit lamp should know how to control all the different settings on it in order to perform a thorough examination of the eyes. This resource may be used instead of a formal lecture and may be followed by a small-group session in the eye examination lane, with a faculty member or other person skilled in the use of the slit lamp in attendance to answer questions and to assist with hands-on practice with the instrument. One limitation is that because this is a passive resource, there is no opportunity to ask questions. Another disadvantage is the lack of nonpatient models demonstrating abnormal slit lamp findings. A simple model has been developed to simulate the presence of inflammatory cells and increased protein in the anterior chamber of the eye and changes in the contour of transparent ocular surfaces.